ARTISTIC AND COMPOSITION CHARACTERISTICS OF MODELS COLLECTION OF WOMEN’S CLOTHES IN MILITARY STYLE - Луцкер, Т. В.; Винничук, М. С.; Колосніченко, О. В.; Піддубна, О. О.; Лазарчук, М. А. (Art and Design, 2019)
Study of the artistic design features of the models of the creative collection of modern women’s clothing using military style. Development of compositional and harmonious and constructive-technological solutions for products of the author’s collection. To achieve this goal, a system-structural, morphological analysis, a compositional-constructive method of research are applied. Sketches are made using the Xara X graphical editor. The evolution of the form, color combinations and the structure of the decoration of products in military style has been studied. Artistic and compositional and structural features of the collection of modern women’s clothing in military style, taking into account modern technologies and materials, are defined and characterized. The structural, texture and plastic characteristics of the costume in the military style are analyzed, the characteristics characteristic of the style are highlighted and introduced into the articles of the collection. The general features of the models of the collection are systematized and the elements characteristic of the military style are structured. Practical significance. The origin of the military style, its features, the obligatory compositional elements of clothing are described. Analyzed fashion trends, considered models of collections and witnessed the main characteristics inherent in this style. Analyzed the characteristic techniques and elements of clothing. The items are decorated with a manual print with the help of artistic painting with paint. Stages are described, recommendations are given on how to care for a product with printed image on textiles. Illustrated creative sketches of women’s sets using artistic painting. Produced models of the author’s collection of women’s clothing and presented at the international competition of young designers.